Monitoring of radon concentration for different building types in Covenant University, Nigeria. Issue 1 (1st January 2020) - Usikalu, M. R.; Onumejor, C. A.; Achuka, J. A.; Akinpelu, A.; Omeje, M.; Adagunodo, T. A.
Abstract: Radon monitoring is essential in determining the actual level of exposure in buildings. Of all the reviewed works on indoor radon level, little to none was done on comparative radon concentration study of different building structures in the study area. A comparative study of the indoor radon concentration of different building types; such as glass house, bricks and basement house structures were done to evaluate sustainable radon level using radon detector (RAD7) machine. The mean radon concentration for glass house, brick house and basement house are 14.96, 10.74 and 144.61 Bqm −3, respectively. Glass house radon concentration range is from 11.03 to 17.46 Bqm −3 . The radon concentration measured ranged from 6.62 to 20.85 Bqm −3 for bricks house structure. Basement structure radon concentration ranges from 15.75 to 614.52 Bqm −3 . It was observed from the study that the mean radon concentration measured from the basement structure was above the recommended limit by a factor of 4. The estimated annual effective doses are 0.377, 0.271 and 3.644 mSvy −1 for glass, brick and basement houses, respectively. The study concluded that possible health risk is associated to basement structure that has limited ventilation than glass and bricks house with easy access to natural ventilation outlet. It is therefore recommended that adequate ventilation be put in place in basement house.